P27/SKP-2 Histochemical Profile is Relevant to Malignant Salivary Gland Tumors (MST) Histogenesis and Tumor Grade - Akrish, Sharon (Springer US, 2011)
Malignant salivary gland tumors (MST) represent over more than 24 distinct morphological subtypes. Most high grade tumors arise from the excretory duct portion of the salivary gland apparatus; the remainder from the intercalated duct portion. Altered p27/skp-2 expression has been associated with tumor aggressiveness and histologic differentiation. In our study, we analyzed p27/skp-2 expression proteins on series of malignant salivary gland tumors in order to assess their value as a histogenetic marker, which is relevant to tumor grade. 61 MST cases were segregated by proposed histogenesis and immunohistochemistry was performed using antibodies directed against p27 and skp-2. MST of proposed intercalated duct origin (n = 27) showed strong p27 expression (n = 25/27; 93%) in the vast majority of cases and all cases weakly expressed skp-2. MST of proposed excretory duct origin (n = 32) showed strong p27 expression (n = 18/32; 56%) and moderately strong/strong skp-2 expression (n = 18/32; 56%), respectively, in over half the cases. MST of intercalated duct origin showed evident p27/skp-2 inverse correlation. Differences in p27/skp-2 expression among the MST subtypes correlated with histogenesis and tumor grade, which reinforces the notion that tumor behavior is relevant to the portion of the salivary gland unit from which they arise. MST of proposed intercalated duct origin strongly expressed p27, and not skp-2, unlike MST of proposed excretory duct origin. The immunohistochemical profile of high grade mucoepidermoid carcinoma was distinct from its low/intermediate grade counterparts, suggesting a separate identity. These results may influence future decision making when formulating workable MST categorization schemes. Further studies on a larger series of MST are warranted in order to support the value of our findings.